A Hodge dual for soldered bundles - Lucas, Tiago Gribl [UNESP]; Pereira, J. G. [UNESP] (Iop Publishing Ltd, 2009)
In order to account for all possible contractions allowed by the presence of the solder form, a generalized Hodge dual is defined for the case of soldered bundles. Although for curvature the generalized dual coincides with the usual one, for torsion it gives a completely new dual definition. Starting from the standard form of a gauge Lagrangian for the translation group, the generalized Hodge dual yields precisely the Lagrangian of the teleparallel equivalent of general relativity, and consequently also the Einstein-Hilbert Lagrangian of general relativity.